PMP22 related congenital hypomyelination neuropathy. Issue 1 (1st January 2001) - Fabrizi, G M; Simonati, A; Taioli, F; Cavallaro, T; Ferrarini, M; Rigatelli, F; Pini, A; Mostacciuolo, M L; Rizzuto, N
Abstract : The peripheral myelin protein 22 (PMP22) is a tetraspan membrane protein which is localised in the compact myelin of the peripheral nerves. In fibroblasts, where it was originally identified as growth arrest related factor 3 (Gas3), PMP22 has been shown to modulate cell proliferation; in the peripheral nervous system its roles are still debated. The duplication of PMP22 is the most common cause of the demyelinating form of the autosomal dominant Charcot-Marie-Tooth neuropathy (CMT1A); rarer missense mutations of PMP22 also cause CMT1A or severe dehypomyelinating neuropathies of infancy grouped under the heading of Dejerine-Sottas syndrome (DSS). Here, a sporadic patient affected with DSS is described; nerve biopsy disclosed a picture of hypomyelination/amyelination with basal laminae onion bulbs and no florid demyelination and it was consistent with congenital hypomyelination neuropathy (CHN); molecular analysis disclosed a novel point mutation of PMP22 that causes a non-conservative arginine for cysteine substitution at codon 109, in the third transmembrane domain. CHN is the rarest and severest form of DSS and it is thought to reflect dysmyelination rather than demyelination. The reported case suggests that missense point mutations may alter a putative role of PMP22 in modulating Schwann cell growth and differentiation.